2015
DOI: 10.1155/2015/915243
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 2 Induces a Phenotypic Switch in Macrophage Polarization Favoring an M2 Anti-Inflammatory State

Abstract: Inflammatory processes are involved in atherosclerosis development. Macrophages play a major role in the early atherogenesis, and they are present in the atherosclerotic lesion in two phenotypes: proinflammatory (M1) or anti-inflammatory (M2). Paraoxonase 2 (PON2) is expressed in macrophages, and it was shown to protect against atherosclerosis. Thus, the aim of our study was to analyze the direct effect of PON2 on macrophage inflammatory phenotypes. Ex vivo studies were performed with murine peritoneal macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…However, unlike DTT, pre-treatment with Tn prevents LPS-mediated M1-like stimulation of RAW 264.7 mouse macrophage cells (Figure 1B and 1C ) and prevented macrophage-mediated endocytosis of breast cancer cells (Figure 1D ). Previous reports showed that DTT and ER chaperones stabilize paraoxonase 2 (PON2) that may promote a more M2-like phenotype in atherosclerosis [ 26 , 27 ], which was not observed in the current study. Whether these differential effects on macrophage plasticity observed by chemical inducers of UPR are due to the differing potency of UPR stimulation (Figure 1A ), the possible requirement of glycosylated protein biosynthesis for macrophage stimulation [ 28 ] or the highly reductive basal redox state existing in macrophages that may curtail DTT efficacy are still unclear [ 29 ].…”
Section: Discussioncontrasting
confidence: 87%
“…However, unlike DTT, pre-treatment with Tn prevents LPS-mediated M1-like stimulation of RAW 264.7 mouse macrophage cells (Figure 1B and 1C ) and prevented macrophage-mediated endocytosis of breast cancer cells (Figure 1D ). Previous reports showed that DTT and ER chaperones stabilize paraoxonase 2 (PON2) that may promote a more M2-like phenotype in atherosclerosis [ 26 , 27 ], which was not observed in the current study. Whether these differential effects on macrophage plasticity observed by chemical inducers of UPR are due to the differing potency of UPR stimulation (Figure 1A ), the possible requirement of glycosylated protein biosynthesis for macrophage stimulation [ 28 ] or the highly reductive basal redox state existing in macrophages that may curtail DTT efficacy are still unclear [ 29 ].…”
Section: Discussioncontrasting
confidence: 87%
“…Transfection of human PON2 into macrophages from PON2 −/− mice inhibited the induction of a pro-inflammatory M1 phenotype and promoted M2 phenotypic differentiation. These data suggest that PON2 inhibits the differentiation of monocytes to a pro-inflammatory phenotype and can act as a switch from an M1 to an M2 phenotype in macrophages (44). …”
Section: Paraoxonase Macrophage Phenotype and Resolution Of Inflammamentioning
confidence: 97%
“…PON2 also regulates macrophage differentiation (44). MPMs isolated from PON2 −/− mice display a pro-inflammatory phenotype (increased TNFα, IL-6 and arginase II) compared to wild-type mice (44).…”
Section: Paraoxonase Macrophage Phenotype and Resolution Of Inflammamentioning
confidence: 99%
See 2 more Smart Citations